Shape optimal design for a fluid-heat coupled system - Chenais, Denise; Monnier, Jérôme; Vila, Jean-Paul (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the shape optimal design problem for a fluid-heat coupled system used in the car industry. For modelling, we assume that the flow is stationary, potential and incompressible, and we consider the thermal transfer by convection, diffusion and radiation with multiple reflexions. The whole model is a non-linear integro-differential system of two partial differential equations and one integral equation.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka